Analysis of the Effect of Cooperative Learning on PAI Learning Outcomes: A Meta-Analysis - Sitti Aisyah Mu'min; Jumarddin La Fua (Dirasah: Jurnal Pendidikan Islam, 2026)
This study aims to analyze the effect of cooperative learning on PAI learning outcomes using meta-analysis. This study is quantitative in nature and involves statistical procedures. Data were collected through coding techniques. Strict inclusion-exclusion criteria were used to ensure that only relevant and high-quality studies were included in the meta-analysis synthesis. These criteria ensured methodological consistency and the validity of the meta-analysis results in measuring the effect of cooperative learning on PAI learning outcomes. The collected articles were read (full text) and then entered into an extraction table to be selected by matching the inclusion-exclusion criteria. A total of 43 articles were collected, but only 23 articles met the criteria for meta-analysis. The data were analyzed using Cohen's formula to determine the effect size. The results of the study found an effect size of 2.13, which is in the very large effect category, indicating that the cooperative model is very effective for PAI learning outcomes. Thus, the results of this meta-analysis reinforce the importance of applying cooperative learning as a pedagogical strategy in improving Islamic religious education learning outcomes.